Management of Free Health Services in Hospital - Siti Mardiyanti; Dewi Rahayu; Ahmad Karbito; Atikah Adyas (Indonesian Journal of Global Health Research, 2021)
The Government of Indonesia is obliged to provide guarantees for the fulfillment of the right to a healthy life for every citizen by enforcing the Social Security Administration (BPJS) for Health. The success of hospitals in carrying out their functions is marked by an increase in the quality of hospital services. To implement the implementation of SJSN in the BPJS program, the phenomenon of existing problems where the management of free health services in hospitals has not been carried out optimally, seeing some complaints in the community, therefore it is necessary to study the management of health services in terms of input, process and output. and 5M management at Tjokrodipo Hospital, Bandar Lampung City. This study aims to determine and describe the Management of Free Health Services at Tjokrodipo Hospital, Bandar Lampung City in 2021. This research is a qualitative study with a descriptive approach. The time of the study was carried out from May to June 2021 in Tjokrodipo Hospital Bandar Lampung Research subjects were selected using purposive sampling technique, researchers used data triangulation techniques and data processing carried out in this study was source triangulation. not available for BPJS patients, so patients are advised to look for other dispensaries, medical equipment such as patient beds are still lacking because during the pandemic, the availability of health human resources (HR), such as dentists and specialists are not in accordance with class C hospital standards, patients feel that the free health services provided are not good, the average patient complains of a lack of equipment such as uncomfortable beds and rooms because there are many patients.